Women, Bangladesh and international security : methods, discourses, and policies - Ahmed, Imtiaz, 1958-; Forum on Women in Security and International affairs (Bangladesh); Bangladesh Freedom Foundation (Dhaka : The University Press, 2004)
Papers presented at a training workshop of Forum on Women in Security and international Affairs held at Dhaka in 2001; sponsored by Bangladesh Freedom Foundation.
Includes bibliographical references and index.
Keywords: Women's rights -- Bangladesh; Women and peace -- Bangladesh; Women -- Bangladesh -- Social conditions